2021
DOI: 10.1002/agj2.20556
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth regulator and low‐dose herbicide programs for annual bluegrass seedhead suppression in fairway and athletic‐height turf

Abstract: I n t e g r a t e d Tu r f g r a s s M a n a g e m e n t : We e d B i o l o g y a n d C o n t r o l

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…These results are consistent with those observed after flumioxazin and oxadiazon were applied during mid-bermudagrass-transition on non-putting green, hybrid bermudagrass (Johnson 1976;Reed and McCullough 2014;Reed et al 2015). Additionally, these results align with preliminary reports of endothall activity on fairway-height hybrid bermudagrass, in which endothall applications were more injurious to hybrid bermudagrass when applied at higher rates to actively growing hybrid bermudagrass (Peppers and Askew 2022). Methiozolin applied at 1,000 g ai ha −1 at site-years MT3 and MT5 was the only treatment outside of endothall to significantly reduce hybrid bermudagrass NDVI relative to the nontreated control.…”
Section: Hybrid Bermudagrass Tolerance To Herbicides Applied During M...supporting
confidence: 89%
See 2 more Smart Citations
“…These results are consistent with those observed after flumioxazin and oxadiazon were applied during mid-bermudagrass-transition on non-putting green, hybrid bermudagrass (Johnson 1976;Reed and McCullough 2014;Reed et al 2015). Additionally, these results align with preliminary reports of endothall activity on fairway-height hybrid bermudagrass, in which endothall applications were more injurious to hybrid bermudagrass when applied at higher rates to actively growing hybrid bermudagrass (Peppers and Askew 2022). Methiozolin applied at 1,000 g ai ha −1 at site-years MT3 and MT5 was the only treatment outside of endothall to significantly reduce hybrid bermudagrass NDVI relative to the nontreated control.…”
Section: Hybrid Bermudagrass Tolerance To Herbicides Applied During M...supporting
confidence: 89%
“…Endothall is currently registered in Australia for annual bluegrass control in turf systems with no restrictions against its use on hybrid bermudagrass golf greens (Anonymous 2020). Endothall's effectiveness to control annual bluegrass has been limited by cool-season turfgrass phytotoxicity (Peppers et al 2021). Although peer-reviewed studies have not reported endothall effects on bermudagrass turf in managed turf systems, bermudagrass ( Cynodon dactylon L.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pest management practices that golf course superintendents rely on the most were plant growth regulators (PGRs) and biological control practices, although reliance on biological control practices declined by nearly 50% from 2015 to 2021. Plant growth regulators have been shown to suppress weeds (Beam and Askew 2017), suppress seed head production (Peppers et al 2020), and occasionally reduce disease severity (Inguagiato et al 2010). Many PGRs are naturally occurring and possess a nontoxic mode of action (i.e., gibberellins, indole-3-butyric acid, and ethylene) and, thus, are not classified as conventional pesticides but rather biological pesticides by the US Environmental Protection Agency (Reilly et al 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Plant growth regulators (PGRs) are regularly utilized for turfgrass growth suppression, increasing turfgrass green color, enhancing abiotic stress tolerance, increasing turfgrass stand density, and reduced plant water usage (Baldwin et al 2009;Beam and Askew 2005;King et al 1997;McCarty et al 2011;McCullough et al 2005). Paclobutrazol, ethephon, and flurprimidol are also regularly utilized for selective annual bluegrass (Poa annua L.) seedhead suppression (Askew 2017;Peppers et al 2021;Reicher et al 2020) or control (Johnson and Murphy 1995;Reicher et al 2015) in turf. These PGRs reduce the competitive advantage of annual bluegrass relative to creeping bentgrass (Johnson and Murphy 1996).…”
Section: Introductionmentioning
confidence: 99%